The Cultivation of Information Infrastructures for International Trade: Stakeholder Challenges and Engagement Reasons - Knol,Arjan (Universidad de Talca, 2018)
Abstract: The development of information infrastructures for international trade to improve supply chain visibility and security has gained momentum due to technological advances. An information infrastructure is a shared, open, and evolving assemblage of interlinked information systems providing distinct information technology capabilities. Examples of information infrastructures are the internet, electronic market places and music platforms. Information infrastructures can be highly beneficial as shown by the aforementioned examples, yet often fail to deliver expected benefits. This research focuses on the cultivation of information infrastructures which refers to a softer, less disruptive design approach compared to traditional design approaches in which systems are defined through specified functional requirements within strict boundaries. Drawing on different stakeholder views within a European Union project for international trade, this research provides a taxonomy of twelve cultivation challenges and four engagement reasons one can expect in the design phase of information infrastructures. Organizational theory is used to discuss underlying explanations. The paper concludes that the cultivation of an information infrastructure for international trade could be highly rewarding, yet is a challenging and long-lasting endeavor which requires multi-disciplinary expertise. Practitioners can use the insights provided by this research to increase their understanding of information infrastructure cultivation to ultimately increase adoption rates.